High-thermal-conductivity polymer-based composite diffuse reflection film as well as preparation method and application thereof

Through mechanical chemical modification, the combination of inorganic filler and polymer matrix was prepared to produce a highly thermal conductivity polymer matrix composite diffuse reflection film, which solved the problem of degradation in the performance of polycarbonate film during processing, and achieved excellent optical, mechanical and Thermal properties, suitable for a variety of high thermal conductivity applications.

CN119220059APending Publication Date: 2024-12-31CENT SOUTH UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411335748.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the processing process, the existing polycarbonate films are broken due to the special surface properties of inorganic powder particles, which affects the optical and physical properties. The high filler content will lead to a decrease in light transmittance, making it difficult to develop good optical Performance and high intensity diffuse reflective film.

Method used

Using a highly thermally conductive polymer matrix composite diffuse reflection film, the combination of inorganic filler and polymer matrix is ​​treated by mechanochemical modification to prepare films with excellent optical, mechanical and thermal properties, including the use of inorganic filler and modifier and organic solvents. After mechanical chemical modification, the polymer matrix is ​​uniformly coated and dried to form a composite diffuse reflection film with a thickness of 0.1 to 2000 μm.

Benefits of technology

It significantly improves the diffuse reflection effect, thermal conductivity and wear resistance of the film, maintains excellent transmittance and reflectivity, and is suitable for transparent projection screens, OLED screens and other fields with high thermal conductivity requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220059A_ABST
    Figure CN119220059A_ABST
Patent Text Reader

Abstract

The invention provides a high-thermal-conductivity polymer-based composite diffuse reflection film as well as a preparation method and application thereof. The film comprises the following components in parts by weight: 100 parts of polymer matrix, 0.001-20 parts of inorganic filler, 0.001-3 parts of modifier and 50-400 parts of organic solvent. The preparation method of the film comprises the following steps: mixing an inorganic filler, a modifier and a part of an organic solvent, and carrying out mechanochemical modification to obtain a solution A; mixing the polymer matrix with the remaining organic solvent, oscillating and dissolving to obtain a solution B; and mixing the solution A and the solution B at room temperature, uniformly coating a clean substrate with the mixture, standing and drying to obtain the coating. According to the invention, a large amount of modified inorganic particles are compounded with a polymer film substrate, so that the optical, mechanical and thermal properties of the film are greatly improved, and particularly, excellent diffuse reflection effect and heat conduction effect are realized. The wear resistance is also remarkably improved, and excellent diffuse reflection and high transmittance can still be kept after a friction wear experiment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diffuse reflection films, and in particular to a high-thermal-conductivity polymer-based composite diffuse reflection film and a preparation method and application thereof. Background Art

[0002] As one of the five major engineering plastics, polycarbonate (PC) not only has good light transmittance, but also has excellent impact resistance, heat resistance, cold resistance and electrical insulation performance. The water absorption rate and product molding shrinkage rate of polycarbonate film are low, and the creep resistance is excellent. Therefore, the size of the product is stable under different temperature and humidity conditions, and the application range of polycarbonate film products is wide. The polycarbonate film prepared with polycarbonate as the matrix has good comprehensive properties such as high strength, stable chemical properties and strong weather resistance. The polycarbonate film without the introduction of coloring elements for doping is colorless and transparent, with a light transmittance of more than 90%, which is suitable for use as a light-transmitting material or as a basic material for optical films. Polycarbonate film materials can be used in transparent display boards, projection displays of elevator / high-speed rail / subway boxes / window glass, short-focus projection displays of eyeglass lenses, optical modification of OLED screens, and hydrophobic and optical performance designs of mobile phone films in today's commercial fields.

[0003] Inorganic powder particles, such as aluminum oxide, silicon oxide (including white carbon black), titanium oxide, zinc oxide, zirconium oxide, bismuth oxide, aluminum carbide titanate, barium titanate, indium tin oxide, diamond, hexagonal boron nitride, cubic boron nitride, aluminum nitride, silicon nitride, heavy calcium, light calcium, talc, kaolin, wollastonite, mica, calcite, etc., have the advantages of high whiteness, strong hiding power, high reflectivity, stable chemical properties, etc., and are widely used in the fields of coatings, covering pigments, light reflective fillers, etc. In particular, the polycarbonate light reflective composite material prepared with micro / nano inorganic particles as light reflective fillers of polycarbonate substrate has good optical properties. However, during the processing, due to the special properties of its surface, the breakage of the polycarbonate molecular chain will be accelerated, causing serious thermal degradation, thereby affecting the optical and physical properties of the reflective film, so the inorganic particles need to be surface treated before preparing the light reflective film.

[0004] In recent years, there have been reports on the research of polycarbonate films in China, such as the patent application document of Suzhou Ogilvy Optical Materials Co., Ltd., entitled "A method for manufacturing a polycarbonate optical panel for LCD TV with anti-reflection and anti-transmittance" (publication number CN101885233A), the patent document of Hefei Jieshijie New Materials Co., Ltd., entitled "An environmentally friendly flame-retardant and scratch-resistant polycarbonate resin and its preparation method" (publication number CN102558808B), and the patent document of Hubei Engineering College, entitled "A high-strength and high-transmittance polycarbonate film with wear-resistant surface for liquid crystal and its preparation method" (publication number CN105647148A), etc., all of which have been reported to varying degrees. At present, domestic research basically improves the abrasion resistance and mechanical properties of polycarbonate by adding inorganic or organic fillers, but the improvement effect is not particularly obvious. This is mainly because when the filler content is greater than 15%, the light transmittance of polycarbonate is often greatly reduced. In addition, there are few research reports on adding inorganic particles such as Al2O3, TiO2, SiO2, and nanodiamond into polycarbonate to prepare light-reflecting films.

[0005] Therefore, in the art, it is desired to develop a diffuse reflection film having good comprehensive properties of good optical properties and high strength, and to provide a preferred preparation process. Summary of the invention

[0006] The present invention provides a high thermal conductivity polymer-based composite diffuse reflection film and a preparation method and application thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.

[0007] In order to achieve the above-mentioned object, an embodiment of the present invention provides a high thermal conductivity polymer-based composite diffuse reflection film, and the film comprises the following components in parts by weight:

[0008] 100 parts of polymer matrix, 0.001 to 20 parts of inorganic filler, 0.001 to 3 parts of modifier, and 50 to 400 parts of organic solvent.

[0009] Preferably, the polymer matrix is ​​one or more of aliphatic polycarbonate, aromatic polycarbonate, epoxy acrylic resin, acrylic polyurethane resin, acrylic amino resin, and thermoplastic polyurethane. More preferably, the aromatic polycarbonate is bisphenol A polycarbonate; the epoxy acrylic resin is novolac epoxy acrylate; and the acrylic polyurethane resin is two-component acrylic polyurethane.

[0010] Preferably, the inorganic filler includes one or more of zirconium oxide, silicon carbide, indium tin oxide, diamond, cubic boron nitride, garnet, aluminum nitride, silicon nitride, and vaterite. More preferably, the average diameter of silicon carbide grains is 10nm-3μm; the average diameter of garnet grains is 200nm-5μm; the average diameter of cubic boron nitride grains is 10-800nm; diamond uses detonation nanodiamond or submicron / nanoscale static pressure diamond, and the average grain diameter is 3-800nm; the average diameter of aluminum nitride grains is 20nm-2μm.

[0011] Preferably, the organic solvent is one or more of dichloromethane, dichloroethane, n-heptane, n-pentane, n-hexane, n-heptane, n-octane, gasoline, petroleum ether, turpentine, benzene, toluene, chlorobenzene, methanol, isopropanol, and acetone.

[0012] Preferably, the modifier is one or more of a titanate coupling agent, an aluminate coupling agent, a silane coupling agent, a zirconate coupling agent, a fatty acid, and a fatty amine. More preferably, the aluminate coupling agent is DN-827; the silane coupling agent is KH-570; and the titanate coupling agent is TMC-114 (38S).

[0013] Preferably, the thickness of the high thermal conductivity polymer-based composite diffuse reflection film is 0.1-2000 μm. More preferably, the thickness of the high thermal conductivity polymer-based composite diffuse reflection film is 1-500 μm.

[0014] Based on a general concept of the invention, an embodiment of the present invention provides a method for preparing a high thermal conductivity polymer-based composite diffuse reflection film, comprising the following steps:

[0015] S1: mixing an inorganic filler, a modifier and a portion of an organic solvent, and subjecting the mixture to mechanochemical modification to obtain a solution A;

[0016] S2: mixing the polymer matrix and the remaining organic solvent, shaking and dissolving them, to obtain solution B;

[0017] S3: Mix solution A and solution B at room temperature and evenly apply them on a clean substrate, place them and dry them.

[0018] Preferably, the inorganic powder filler accounts for 0.001wt.% to 40wt.% of the mass of the high thermal conductive polymer-based composite diffuse reflective film; the average grain diameter of the inorganic powder is 3nm-5μm, and the average particle size of the particles or particle agglomerates is 3nm-100μm.

[0019] Preferably, the mechanochemical modification includes one or more of ball milling, ultrasound, and high-dispersion emulsification shearing.

[0020] The ball milling process uses one or more of a sand mill, a stirred mill, and a planetary mill, the ball milling medium used is 0.01mm-6mm zirconium oxide or aluminum oxide, the linear speed is 10-3000 rpm, and the ball milling time is 5-4320 minutes;

[0021] The ultrasonic frequency is 20-400kHz, the power is 200-6000W, and the ultrasonic time is 5-1800 minutes;

[0022] The high-dispersion emulsification shearing motor power is 1.0-40kW, the motor speed is 1000-3000 rpm, and the dispersion time is 1-120 minutes.

[0023] The mixing method of solution A and solution B is a same-matrix solution blending method, and the film-forming and drying conditions of the blended solution are any one of the following working conditions: film formation in an open environment at room temperature; film formation in a semi-open container by controlling the temperature to 50-80°C and the humidity to 25%-60%; film formation in an inert atmosphere by controlling the temperature to 50-80°C and the humidity to 25%-60%; film formation in a low vacuum environment by controlling the temperature to 50-80°C and the vacuum degree of the system to 0.0001-0.5Mpa.

[0024] The substrate is a glass plate, a PC board or a silicon wafer.

[0025] The embodiments of the present invention further provide the use of the above-mentioned high thermal conductivity polymer-based composite diffuse reflection film or the high thermal conductivity polymer-based composite diffuse reflection film obtained by the above-mentioned preparation method in light-transmitting projection materials.

[0026] The above scheme of the present invention has the following beneficial effects:

[0027] (1) The present invention uses a large amount of modified inorganic particles to compound a polymer film matrix, which greatly improves the optical, mechanical and thermal properties of the film, especially achieving excellent diffuse reflection and thermal conductivity. At the same time, the wear resistance of the modified film is significantly improved, and after the friction and wear test, it can still maintain excellent diffuse reflection (reflectivity) and high transmittance.

[0028] (2) The polymer film modification method of the present invention is simple to operate and easy to implement. It provides a new feasible solution for inorganic thermal conductivity (thermal conductivity is increased, so that the heat generated by the energy of the projected light (visible light has energy) can be transferred to the surface for release, ensuring the service life of the material and the composite of filler and polymer matrix. The thermal conductivity of the modified polymer film is significantly improved, and it can be widely used in various fields with high thermal conductivity requirements.

[0029] (3) The present invention is particularly suitable for use as a transparent projection screen. The term "transparent projection screen" refers to a sticky transparent film that can be pasted on the surface of a corresponding material (such as glass, metal, etc.) like a "sticker", and can turn any material surface into a projection screen, such as transparent display boards that can be seen everywhere on the streets, high-speed rail or subway car windows and projection displays inside elevators. In addition, the film prepared by the present invention can also be used in short-focus projection displays of eyeglass lenses, optical modification of OLED screens, design of hydrophobic and optical properties of mobile phone protective films, and aerospace and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 is the diffuse reflectance spectrum of the transparent film in the ultraviolet-visible light band of the projection film obtained in Example 1 of the present invention;

[0032] Figure 2 This is a comparison diagram of diffuse reflectance spectra of transparent films in the ultraviolet-visible light band of the projection film obtained in Example 2 of the present invention and a pure film;

[0033] Figure 3 This is a photo of the light transmittance of a thin film obtained by adding different contents of inorganic fillers in Example 2 of the present invention;

[0034] Figure 4 This is the relationship between the light transmittance and wavelength of the film obtained by adding different contents of inorganic fillers in Example 4 of the present invention.

[0035] Figure 5 1 is a SEM photograph of a projection film obtained in one embodiment of the present invention. DETAILED DESCRIPTION

[0036] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0037] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0039] In view of the existing problems, the present invention provides a high thermal conductivity polymer-based composite diffuse reflection film and a preparation method and application thereof.

[0040] Example 1

[0041] A high thermal conductivity polymer-based composite diffuse reflection film, comprising the following components in parts by weight:

[0042] 100 parts of phenolic epoxy acrylate;

[0043] Garnet 10 parts;

[0044] Aluminate coupling agent (DN-827) 0.5 parts;

[0045] 300 parts of ethylene dichloride.

[0046] The above-mentioned mechanochemical modification method of garnet powder comprises the following steps:

[0047] The garnet and aluminate coupling agent (DN-827) raw materials were weighed according to the above weight parts, mixed with 100 parts of dichloroethane solution, and ground with a sand mill to achieve particle size homogenization and surface activation of the garnet particles. The rotor speed of the sand mill was 2000 rpm, the sand milling was performed for 2 hours, and the ground slurry was ultrasonically stirred for 10 minutes, and the obtained slurry was slurry A.

[0048] Preparation of novolac epoxy acrylate matrix material: 100 parts of novolac epoxy acrylate and 200 parts of ethylene dichloride were mixed and shaken to dissolve, and the resulting slurry was B slurry.

[0049] The mixed solution obtained by mixing the above-mentioned A slurry and B slurry evenly is placed in an argon atmosphere, and is spin-coated at 50-80°C with a humidity controlled in the range of 25%-60% to form a film. After the dichloroethane solvent is evaporated in an open environment, a film with a thickness of 50 μm is obtained.

[0050] Example 2

[0051] A high thermal conductivity polymer-based composite diffuse reflection film, comprising the following components in parts by weight:

[0052] 100 parts of bisphenol A polycarbonate;

[0053] 1 part of detonation nanodiamond;

[0054] Titanate coupling agent (TMC-114 (38S)) 0.1 part;

[0055] 200 parts of petroleum ether.

[0056] The above-mentioned mechanochemical modification method of detonation nanodiamond comprises the following steps:

[0057] Detonation nanodiamond and titanate coupling agent (TMC-114 (38S)) raw materials were weighed according to the above weight parts, mixed with 100 parts of petroleum ether solution, and ball-milled by a planetary mill at an orbital speed of 350 rpm for 8 hours. The ground slurry was then ultrasonically stirred for 20 minutes to obtain slurry C.

[0058] Preparation of bisphenol A polycarbonate matrix material: 100 parts of bisphenol A polycarbonate and 100 parts of petroleum ether were mixed and shaken to dissolve, and the obtained slurry was D slurry.

[0059] The mixed solution obtained by mixing the above C slurry and D slurry evenly was spin-coated in a semi-open environment at 60° C. with humidity controlled at 40%. After the petroleum ether solvent was evaporated and dried, a film with a thickness of 50 μm was obtained.

[0060] Example 3

[0061] A high thermal conductivity polymer-based composite diffuse reflection film, comprising the following components in parts by weight:

[0062] Two-component acrylic polyurethane 100 parts;

[0063] Green silicon carbide 5 parts;

[0064] 0.5 parts of aluminate coupling agent;

[0065] 100 parts of petroleum ether;

[0066] 200 parts of n-hexane.

[0067] The above-mentioned mechanochemical modification method of green silicon carbide powder comprises the following steps:

[0068] Green silicon carbide powder and aluminate coupling agent 827 raw materials were weighed by weight, mixed with 100 parts of petroleum ether solution, and ball-milled with a stirred mill. The stirring impeller speed was 1200 rpm, ball-milled for 4 hours, and then the ground slurry was ultrasonically stirred for 30 minutes, and the obtained slurry was E slurry.

[0069] Preparation of two-component acrylic polyurethane matrix material: 100 parts of two-component acrylic polyurethane and 200 parts of normal hexane were mixed and dissolved by shaking, and the obtained slurry was F slurry.

[0070] The mixed solution obtained by mixing the above-mentioned E slurry and F slurry evenly was spin-coated in an inert (nitrogen) atmosphere at 50-80° C. with the humidity controlled at 25%-60%. After the solvent was evaporated and dried, a film with a thickness of 100 μm was obtained.

[0071] Example 4

[0072] A high thermal conductivity polymer-based composite diffuse reflection film, comprising the following components in parts by weight:

[0073] Novolac epoxy acrylate 80 parts;

[0074] Two-component acrylic polyurethane 20 parts

[0075] 5 parts of aluminum nitride;

[0076] Silane coupling agent (KH-570) 0.2 parts;

[0077] 100 parts of petroleum ether;

[0078] 100 parts of n-hexane.

[0079] The above-mentioned mechanochemical modification method of aluminum nitride comprises the following steps:

[0080] Aluminum nitride and silane coupling agent (KH-570) raw materials were weighed by weight, mixed with 100 parts of petroleum ether solution, and ball-milled with a planetary mill at an orbital speed of 350 rpm for 12 hours. The ground slurry was then ultrasonically stirred for 20 minutes. The resulting slurry was G slurry.

[0081] Preparation of the composite polymer matrix material: 80 parts of phenolic epoxy acrylate, 20 parts of two-component acrylic polyurethane and 100 parts of n-hexane are mixed and shaken to dissolve, and the resulting slurry is H slurry.

[0082] The G slurry and the H slurry were mixed evenly, and then the mixed solution was spin-coated in a semi-open environment at 60° C. with humidity controlled at 40%. After the solvent was evaporated and dried, a film with a thickness of 100 μm was obtained.

[0083] Example 5

[0084] A high thermal conductivity polymer-based composite diffuse reflection film, comprising the following components in parts by weight:

[0085] 100 parts of bisphenol A polycarbonate;

[0086] 2 parts of cubic boron nitride;

[0087] 1 part of silicon nitride;

[0088] Titanate coupling agent (TMC-114 (38S)) 0.1 part;

[0089] 300 parts of n-hexane.

[0090] The mechanochemical modification method of cubic boron nitride and silicon nitride comprises the following steps:

[0091] Cubic boron nitride, silicon nitride and titanate coupling agent (TMC-114 (38S)) raw materials were weighed according to the above weight parts, mixed with 150 parts of n-hexane solution, and ball-milled by a planetary mill at a revolution speed of 350 rpm for 12 hours. The ground slurry was ultrasonically stirred for 30 minutes to obtain slurry I.

[0092] Preparation of bisphenol A polycarbonate matrix material: 100 parts of bisphenol A polycarbonate and 150 parts of n-hexane were mixed and shaken to dissolve, and the obtained slurry was J slurry.

[0093] The mixed solution obtained by mixing the above-mentioned I slurry and J slurry evenly was spin-coated in a semi-open environment at 60° C. with the humidity controlled at 50%. After the n-octane solvent was evaporated and dried, a film with a thickness of 50 μm was obtained.

[0094] Comparative Example 1

[0095] The difference from Example 5 is that the inorganic filler is directly added to the polymer matrix without being modified.

[0096] Comparative Example 2

[0097] The difference from Example 5 is that the inorganic filler is alumina.

[0098] Comparative Example 3

[0099] The difference from Example 5 is that the polymer matrix material is PVA.

[0100] Comparative Example 4

[0101] The difference from Example 5 is that the content of the inorganic filler is 0.05 parts.

[0102] Comparative Example 5

[0103] The difference from Example 5 is that the content of the inorganic filler is 40 parts.

[0104] The polymer-based composite diffuse reflective films prepared in Examples 1-5 of the present invention and Comparative Examples 1-4 were used as samples to perform performance tests such as diffuse reflectance (reflectivity), light transmittance, thermal conductivity and weather resistance (reflectivity of the film after irradiation with a 30W ultraviolet lamp (wavelength of 185nm) for 8 hours), and the test results are as follows.

[0105]

[0106] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high thermal conductivity polymer-based composite diffuse reflection film, characterized in that: The film comprises the following components in parts by weight: 100 parts of polymer matrix, 0.001 to 20 parts of inorganic filler, 0.001 to 3 parts of modifier, and 50 to 400 parts of organic solvent.

2. A high thermal conductivity polymer-based composite diffuse reflection film according to claim 1, characterized in that: The polymer matrix is ​​one or more of aliphatic polycarbonate, aromatic polycarbonate, epoxy acrylic resin, acrylic polyurethane resin, acrylic amino resin, and thermoplastic polyurethane.

3. The high thermal conductivity polymer-based composite diffuse reflection film according to claim 1, characterized in that: The inorganic filler includes one or more of zirconium oxide, silicon carbide, indium tin oxide, diamond, cubic boron nitride, garnet, aluminum nitride, silicon nitride, and vaterite.

4. The high thermal conductivity polymer-based composite diffuse reflection film according to claim 1, characterized in that: The organic solvent is one or more of dichloromethane, dichloroethane, n-heptane, n-pentane, n-hexane, n-heptane, n-octane, gasoline, petroleum ether, turpentine, benzene, toluene, chlorobenzene, methanol, isopropanol, and acetone.

5. The high thermal conductivity polymer-based composite diffuse reflection film according to claim 1, characterized in that: The modifier is one or more of a titanate coupling agent, an aluminate coupling agent, a silane coupling agent, a zirconate coupling agent, a fatty acid, and a fatty amine.

6. The high thermal conductivity polymer-based composite diffuse reflection film according to claim 1, characterized in that: The thickness of the high thermal conductivity polymer-based composite diffuse reflection film is 0.1-2000 μm.

7. A method for preparing a high thermal conductivity polymer-based composite diffuse reflection film according to any one of claims 1 to 6, characterized in that: The steps include: S1: mixing an inorganic filler, a modifier and a portion of an organic solvent, and subjecting the mixture to mechanochemical modification to obtain a solution A; S2: mixing the polymer matrix and the remaining organic solvent, shaking and dissolving them, to obtain solution B; S3: Mix solution A and solution B at room temperature and evenly apply them on a clean substrate, leave them to dry, and you are done.

8. The high thermal conductivity polymer-based composite diffuse reflection film according to claim 7, characterized in that: The inorganic powder filler accounts for 0.001wt.% to 40wt.% of the mass of the high thermal conductivity polymer-based composite diffuse reflection film; the average grain diameter of the inorganic powder is 3nm-5μm, and the average particle diameter of the particles or particle agglomerates is 3nm-100μm.

9. The method for preparing a high thermal conductivity polymer-based composite diffuse reflection film according to claim 7, characterized in that: The mechanochemical modification includes one or more of ball milling, ultrasound, and high-dispersion emulsification shearing.

10. Use of the high thermal conductivity polymer-based composite diffuse reflection film as claimed in any one of claims 1 to 6 or the high thermal conductivity polymer-based composite diffuse reflection film obtained by the preparation method as claimed in any one of claims 7 to 9 in light-transmitting projection materials.

Citation Information

Patent Citations

  • Polyimide film and preparation method thereof

    CN103194062A

  • Preparation method of high-transmittance anti-scratch polycarbonate film

    CN104119663A

  • High-thermal-conductivity engineering plastic and preparation method thereof

    CN105623234A

  • Diffuse reflection coating for optical curtain and optical curtain

    CN112575590A

  • Radiation refrigeration film for enhancing diffuse reflection as well as preparation method and application of radiation refrigeration film

    CN118082309A